The Ratio of NT-proBNP to CysC1.53 Predicts Heart Failure in Patients With Chronic Kidney Disease - Wang, Sheng; Li, Ming; Wang, Xiangyu; Luo, Jing; Zou, Yulin; Hu, Yang; Liu, Xingtai; Ao, Hua; Yao, Xueer; Li, Chufeng; Yang, Tingting (Frontiers in Cardiovascular Medicine, 2021)
Background: The N-terminal pro B type natriuretic peptide (NT-proBNP) measurement has brought new insight into the prognosis of heart failure in patients with chronic kidney disease (CKD). However, the NT-proBNP level is easily affected by renal insufficiency, which limits its clinical use. Methods: This study included 292 patients with CKD. Plasma levels of NT-proBNP and cystatin C (CysC) were measured at admission. The echocardiographic parameters were also detected. Patients were divided into the heart failure group and control group based on cardiac function. Associations of cardiac insufficiency with echocardiographic parameters in CKD patients were analyzed by univariate analysis. Binary logistic regression analysis was performed to evaluate the degree of influence of all statistically significant factors for predicting cardiac dysfunction in CKD patients. Pearson correlation analysis was used to analyze the relationship between the NT-proBNP/CysC1.65 ratio and NT-proBNP level. Receiver operating characteristic (ROC) curve analysis was performed to analyze the sensitivity and specificity of the indicators for predicting cardiac dysfunction in CKD patients. Results: An elevated NT-proBNP/CysC1.65 ratio was an independent risk factor for cardiac dysfunction in CKD (odds ratio=1.002, 95% confidence interval: 1.000–1.003, p=0.000). There was no correlation between the NT-proBNP/CysC1.65 ratio and the NT-proBNP level (r=0.376, p=6.909). The area under the ROC curve for the NT-proBNP/CysC1.65 ratio was 0.827 (95% confidence interval: 0.779–0.875), with a cut-off point of 738.125, a sensitivity of 78.47%, and a specificity of 79.73%. Conclusion: The NT-proBNP to CysC1.65 ratio was superior to NT-proBNP alone for predicting cardiac dysfunction in patients with CKD.